2022
DOI: 10.1371/journal.pntd.0010322
|View full text |Cite
|
Sign up to set email alerts
|

What the snake leaves in its wake: Functional limitations and disabilities among snakebite victims in Ghanaian communities

Abstract: Background The estimated five million snakebites per year are an important health problem that mainly affect rural poor populations. The global goal is to halve both mortality and morbidity from this neglected tropical disease by 2030. Data on snakebite morbidity are sparse and mainly obtained from hospital records. Methods This community-based study was conducted among 379 rural residents with or without a history of snakebite in the Ashanti and Upper West regions of Ghana. All participants in the snakebite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…Snakebite envenoming is a neglected tropical disease that kills up to 94 000 people annually ( Kasturiratne et al, 2008 ). The number of patients incurring disability through snakebite is likely of similar magnitude ( Chippaux, 2011 ; Aglanu et al, 2022 ; Habib et al, 2015 ) if not higher, though reliable estimates are still outstanding. Regions where venomous snakebite is most endemic are South- and Middle America, Sub-Saharan Africa, India and the East and South-East Asia-regions ( Kasturiratne et al, 2008 ).…”
Section: The Role and Scope Of Traditional Healers In Snakebite Endem...mentioning
confidence: 99%
See 2 more Smart Citations
“…Snakebite envenoming is a neglected tropical disease that kills up to 94 000 people annually ( Kasturiratne et al, 2008 ). The number of patients incurring disability through snakebite is likely of similar magnitude ( Chippaux, 2011 ; Aglanu et al, 2022 ; Habib et al, 2015 ) if not higher, though reliable estimates are still outstanding. Regions where venomous snakebite is most endemic are South- and Middle America, Sub-Saharan Africa, India and the East and South-East Asia-regions ( Kasturiratne et al, 2008 ).…”
Section: The Role and Scope Of Traditional Healers In Snakebite Endem...mentioning
confidence: 99%
“…As a result, snakebite envenoming is frequently not perceived as a purely biomedical phenomenon, meaning spiritual interpretations often weigh heavily on the treatment-seeking process. In addition, the mental disease burden linked to snakebite, as identified in scientific literature appears to be substantial ( Aglanu et al, 2022 ; Vaiyapuri et al, 2013 ; Arias-Rodríguez and Gutiérrez, 2020 ; Muhammed et al, 2017 ; Wijesinghe et al, 2015 ; Williams et al, 2011 ). For example, levels of depression and post-traumatic stress disorder were found to be as high as 54% and 21%, respectively, among snakebite patients in Sri Lanka ( Williams et al, 2011 ).…”
Section: The Role and Scope Of Traditional Healers In Snakebite Endem...mentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to emphasize that the victim from this case presented both permanent anatomical and functional sequelae that will last throughout his life. Although snakebite numbers are often quantified, their severity, consequences (e.g., disabilities), and impacts are still unknown [ 22 , 30 , 31 ]. Recently, using the World Health Organization Disability Assessment Schedule 2.0 (WHODAS 2.0), Aglanu et al (2022) demonstrated that 35% of snakebite envenomings in regions of Ghana resulted in mild/moderate disabilities [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Snakebite is a neglected public health issue affecting individuals of all ages in many tropical countries [1, 2]. Venom from snakebite is a potentially life-threatening disease associated with severe morbidities and mortalities [3, 4]. Among countries in the tropical and subtropical areas, snakebite has been regarded as a neglected public health issue necessitating rapid attention [1].…”
Section: Introductionmentioning
confidence: 99%